2018
DOI: 10.17113/ftb.56.03.18.5618
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Study and Determination of All-trans Retinol at Carbon Paste Electrode Modified by Surfactant

Abstract: SummaryThe oxidation mechanism of all-trans-retinol (vitamin A1) and its several esters in non-aqueous, aqueous organic mixture, and pure aqueous media was investigated by cyclic voltammetry. The oxidation occurred in several irreversible steps. The calculated highest density of electrons in retinoid molecules which are delocalized over carbon atoms of the five conjugated double bonds (C5-C14) was found in the part of the molecule involved in oxidation processes. The most sensitive oxidation peak (at +0.8 V vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…All ELVs represents more non‐polar lipophilic vitamins than their naturally occurring forms due to the presence of ester functional group [14–16]. They are usually dissolved in pure organic solvents or in their aqueous mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…All ELVs represents more non‐polar lipophilic vitamins than their naturally occurring forms due to the presence of ester functional group [14–16]. They are usually dissolved in pure organic solvents or in their aqueous mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…In a study, researchers developed a DPV technique by which retinol could be detected in modified carbon paste electrode with 30% (w/w) SDS (CPE/SDS) (Žabčíková, Mikysek, et al, 2018). The findings indicated that the electrode surface repelled the organic solvent in the presence of surfactants.…”
Section: Application Of Surfactants In Voltammetric Methodsmentioning
confidence: 99%
“…The Pt:Co/IL/CPE showed LOD of 0.04 μM and the authors also analysed the electrode utility using cabbage and tablet specimens [21]. S. Žabčíková et al [22] used CV to investigate the oxidation mechanism of all-trans retinol and their esters in non-aqueous, aqueous organic mixture, and pure aqueous media. Their most sensitive oxidation peak appearing at +0.8 V vs. Ag/AgCl was used for the development of a new direct voltammetric method based on DPV for the determination of retinol at carbon paste.…”
Section: Electrochemical Sensors For Vitamin Amentioning
confidence: 99%
“…The results showed that modification of CPE using 30 % (by mass) sodium dodecyl sulphate (SDS) has optimal sensitivity. In comparison to the regularly used glassy carbon electrode (GCE), the CPE/SDS demonstrated remarkable progress in retinol electroanalysis, yielding a LOD of 1.3 M [22].…”
Section: Electrochemical Sensors For Vitamin Amentioning
confidence: 99%